European Union and the Refugees. Is Transparent and Timely Communication Enough to Solve a Crisis? - BARBU, Cristina Mihaela; PONEA, Ștefan (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
More than one million migrants and refugees have crossed into Europe Since early 2011, sparking a crisis as countries struggled to cope with the influx. The main reason for the spike in refugees has been the war in Syria, which has caused millions to flee their homes and seek shelter in Europe and in neighboring countries. But many refugees are also fleeing one of the15 conflicts around the world that have erupted or reignited over the last five years, often situations of decades-old instability and conflict like those in Afghanistan, Somalia, Central America and elsewhere. In this paper, we will try to demonstrate that the EU has indeed adopted a strategy of transparency and consistency when it comes to communication. However, one of the questions we feel obliged to formulate an answer to is „Is this helpful? Is transparent communication enough in order to solve or, at least, find a way to solve the problem? Or is there something missing from this strategy?’